Physical activity of children from an child care home (Contemporary problems of physical and health culture, 2022)
The aim of the research was to try to assess the level of physical activity undertaken by children and adolescents from an child care home. The diagnostic survey method was used. 50 people were subjected to the study. After analyzing the research results, it was found that the majority of the surveyed youth willingly undertook physical activity. Cycling, walking and excursions are very popular. The most frequently indicated barrier to taking up physical activity among the respondents is the lack of time and company.